Contemplating violence : critical studies in modern German culture - Engelstein, Stefani, 1970-; Niekerk, Carl (Amsterdamer Beiträge zur neueren Germanistik ;, 2011)
Illuminates the treatment of violence in the German cultural tradition between the French Revolution and the Holocaust and Second World War.